Guidance and Counseling Services in Developing Learner Happiness: Systematic Literature Review - Ari Kurniawan; Mamat Supriatna; Yusi Riksa Yustiana (Institute of Computer Science (IOCS), 2021)
The guidance and counselling service approach in current research is no longer only focused on problems and how to handle them. Still, many have focused on individual strengths and individual optimization. One of them is happiness. This study aims to analyze the effectiveness of guidance and counselling services in developing students' happiness. The method used is Systematic Literature Review by collecting references from various research kinds of literature from both journals and theses and dissertations in the 2015-2021 timeframe. Data analysis used the meta-synthesis method, namely identifying and interpreting the overall research results following the research questions being studied. The findings of this study are that there are various guidance and counselling service interventions in the literature which are analyzed and categorized into several major themes. And the majority of these interventions have a significant and effective effect on developing students' happiness.